(untitled) (International Journal of Petroleum Technology, 2015)
Oil-and-gas-saturated stratum is an integral interrelated system of rocks (minerals) and fluids (oil, gas, and water). Being a «living» fluid-rock system, it is subject to the laws of auto regulation. It is necessary that research and practical efforts be focused on study and control of the oilfield «life».